A construção de mundos online: uma análise da comunidade de fãs de Lost, Darkufo - Trento, Francisco Beltrame (2013)
This dissertation aims to analyze the world-building process as spaces of transmidiatic communication. We listed information from the distinct media utilized on the development of the TV series Lost, including it internal narrative complexity. We studied and classified distinct factors that congregated the user interaction in an online community. We investigated the conditions of meaning production and the discursive and ideological formations enounced in a complex system of communicational interaction. We also observed how the authorfunction acts in collaborative ambient from the web 2.0. This research is qualitative and exploratory, and examines the Darkufo online community, constituted by users that were fans of the TV-series Lost. Based on the netnographic methodology and using the discourse analysis studies, we tried to systematize the processes that involve users and the online community interactive ambient.